A new firefly luciferase with bimodal spectrum: Identification of structural determinants of spectral pH-sensitivity in firefly luciferases - Viviani, Vadim R. [UNESP]; Oehlmeyer, T. L. [UNESP]; Arnoldi, F. G C [UNESP]; Brochetto-Braga, M. R. [UNESP] (Wiley, 2005)
Fireflies emit flashes in the green-yellow region of the spectrum for the purpose of sexual attraction. The bioluminescence color is determined by the luciferases. It is well known that the in vitro bioluminescence color of firefly luciferases can be shifted toward the red by lower pH and higher temperature; for this reason they are classified as pH-sensitive luciferases. However, the mechanism and structural origin of pH sensitivity in fireflies remains unknown. Here we report the cloning of a new luciferase from the Brazilian twilight active firefly Macrolampis sp2, which displays an unusual bimodal spectrum. The recombinant luciferase displays a sensitive spectrum with the peak at 569 nm and a shoulder in the red region. Comparison of the bioluminescence spectra of Macrolampis, Photinus and Cratomorphus firefly luciferases shows that the distinct colors are determined by the ratio between green and red emitters under luciferase influence. Comparison of Macrolampis luciferase with the highly similar North American Photinus pyralis luciferase (91%) showed few substitutions potentially involved with the higher spectral sensitivity in Macrolampis luciferase. Site-directed mutagenesis showed that the natural substitution E354N determines the appearance of the shoulder in the red region of Macrolampis luciferase bioluminescence spectrum, helping to identify important interactions and residues involved in the pH-sensing mechanism in firefly luciferases. © 2005 American Society for Photobiology.
Keywords: luciferase; photoprotein; amino acid sequence; animal; chemistry; consensus sequence; firefly; kinetics; luminescence; metabolism; molecular genetics; pH; sequence alignment; Amino Acid Sequence; Animals; Consensus Sequence; Fireflies; Hydrogen-Ion Concentration; Kinetics; Luciferases; Luminescent Measurements; Luminescent Proteins; Molecular Sequence Data; Sequence Alignment; Lampyridae; Photinus; Photinus pyralis